A comparison of anionic and cationic dye removal efficiency of industrial bauxite waste red-mud. Issue 1 (3rd January 2023) - Atun, Gülten; Ortaboy, Sinem; Tüzün, Elif; Türker Acar, Elif
Abstract: Sorption characteristics of the acid-activated bauxite waste red-mud for Nylomine-Blue and Methylene-Blue were investigated to predict its potential removal ability for anionic-di-anthraquinone and cationic-thiazine-dyes, respectively. Surface characteristics of the red-mud were examined using atomic-force-microscopy, diffuse-reflectance-Fourier-transform, and X-ray-diffraction spectroscopy techniques. Kinetic data obtained at four different temperatures fit well to the pseudo-second-order and homogeneous-surface-diffusion models. The experimental Nylomine-Blue sorption capacity (0.020 mmol/g) is higher than that of Methylene-Blue (0.012 mmol/g) at 288 K but they change oppositely with the temperature and attain 0.013 and 0.043 mmol/g at 318 K, respectively. Experimental equilibrium data for Methylene-Blue and Nylomine-Blue are well predicted by the Freundlich, Langmuir, and Dubinin-Radushkevich isotherm equations. The mean-sorption-energies fall into the ion-exchange range for Methylene-Blue but electrostatic-attraction-forces play a more important role in Nylomine-Blue sorption. These mechanisms were correlated to the pH changes in the sorption process and the differences in the diffuse-reflectance-Fourier-transform spectra of dye-loaded sorbents. The atomic-force-microscopy topography and phase images revealed that the hematite and sodalite appear as hills on the red-mud surface but gibbsite and calcite minerals cover the valleys. The Methylene-Blue molecules are sorbed by ion-exchange in the positively-charged-valleys in dilute solutions but Nylomine-Blue is sorbed specifically on overall surface in whole concentration range. Graphical Abstract: UF0001